KOMERSIALISASI PADA PRODUKTIVITAS LEMBAGA KEUANGAN MIKRO - Nanette Indira Wibowo; Deny Dwi Hartomo (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2017)
The purpose of this study was to determine the effect of commercialization on the productivity of MFIs in Indonesia by using variable profitability consisting of proxies ROA, ROE, NIM and variable liabilities consisting of proxies size of the loan portfolio and leverage. The research is explanatory research with purposive sampling technique in MFIs in Indonesia to use data sources Microfinance Information Exchange from 2010-2015. The samples used in this study were 40 rural banks.Results showed that the profitability and liabilities simultaneously significant positive effect on Yield Rate. And partially, ROE ROA NIM significant positive effect on Yield Rate with a significance level of 5%, 5% and 5%. While the loan portfolio positive effect was not significant to Yield Rate, and leverage negative effect not significant to Yield Rate. Keywords: productivity, microfinance institutions, profitability, liabilities